Gene actions involved in yield and yield contributing traits of chilli (Capsicum annuum L.) - Hasanuzzaman, M.; Golam, F. (2011)
Gene action for yield and yield contributing traits in Chilli (Capsicum annuum L.) was studied in four selected crosses, involving five parents, including their F-1's, F-2's and first back crosses generations. The significant scaling tests (one or more scales in A, B and C) and joint scaling test indicated the presence of digenic epistasis for all the studied traits. Number of fruits and yield per plant were controlled by additive, dominance and epistatic gene action. Complex genetic behavior was observed in all traits. Since the segregating generations did not follow a simple Mendelian inheritance, high selection pressure is expected in later generations due to probable successful exploitation of additive and dominance components. From these observations it is suggested that the selection for the improvement of all traits, particularly yield per plant, should be delayed to the later generations of segregating population in this plant. The modified bulk method of selection is recommended, in which selection is performed after attaining the homozygosity for maximum heterozygous loci. Presence of complementary gene action and prevalence of the high magnitude of non-additive gene effects were found in most of the traits, indicating that heterosis breeding is more effective with high potential in chili.